Universal`s Law Dictionary (New Delhi, 2016)
UNIVERSAL`S LAW DICTIONARY English to Hindi to Urdu (Hindi Script) Hindi to English to Urdu (Hindi Script) Urdu (Hindi Script) to English to Hindi A Reliable Dictionary-cum-Law Referencer of Authenticated English, Hindi and Arabic-Persian mixed Urdu and Latin-Hindi Words and Terms Dansingh Suganchand Choudhary Ex-District and Sessions Judge Ex-Judicial Member, M.P. Arbitration Tribunal, Bhopal , Ex-Principal, R.C. Jaal Vidhi Mahavidyalaya, Ambedkar Nagar (MHOW) M.P. and Author of Indian Penal Code, Interpretation of Statutes, Indian Evidence Act, Glossary (Honoured with First Prize of Government of India and Many More) and Prof. Praveen Kumar Dansingh Choudhary Government State Level P.G. Law College , Bhopal (M.P.) President, National Law Students Forum Introduction by JUSTICE R.C. LAHOTI Former Chief Justice of India Foreword by JUSTICE FAIZANUDDIN Judge, Supreme Court of India
Keywords: Law